2004
DOI: 10.1111/j.1365-2591.2004.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Enterococcus faecalis isolated from canals of root filled teeth with periapical lesions

Abstract: Enterococcus faecalis isolates were completely susceptible, in vitro, to amoxicillin, amoxicillin-clavulanic acid, vancomycin and moxifloxacin. Most isolates were susceptible to chloramphenicol, tetracycline, doxycycline or ciprofloxacin. Erythromycin and azithromycin were least effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
84
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 49 publications
(151 reference statements)
16
84
2
6
Order By: Relevance
“…In our study, susceptibility to antibiotics was assayed by the E-test method that provides easy handling, interpretation, and reliability [41]. E. faecalis isolates showed resistance of 14, 9 and 4.5% to tetracycline, ciprofloxacin and azithromycin, respectively, in agreement with previously reported results [12,[42][43][44]. Importantly, in this study we found 32% of the E. faecalis isolates with intermediate susceptibility to vancomycin that is an antibiotic recommended intravenously to treat a number of bacterial infections caused by resistant strains in hospitalized patients.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In our study, susceptibility to antibiotics was assayed by the E-test method that provides easy handling, interpretation, and reliability [41]. E. faecalis isolates showed resistance of 14, 9 and 4.5% to tetracycline, ciprofloxacin and azithromycin, respectively, in agreement with previously reported results [12,[42][43][44]. Importantly, in this study we found 32% of the E. faecalis isolates with intermediate susceptibility to vancomycin that is an antibiotic recommended intravenously to treat a number of bacterial infections caused by resistant strains in hospitalized patients.…”
Section: Discussionsupporting
confidence: 80%
“…can be associated with chronic periodontal diseases and endodontic infections [6,7].The presence of enterococci within the root canal has been associated with persistent endodontic and periapical infections, being E. faecalis the most prevalent specie [8][9][10][11]. E. faecalis play an important role in post-treatment diseases because this specie can show high resistance to conventional antimicrobial agents, such as sodium hypochlorite, chlorhexidine, and calcium hydroxide [12][13][14]. In addition, certain clinical isolates of E. faecalis recovered from root canal infections demonstrated resistant to several antibiotics recommended for dental procedures, such as benzylpenicillin, ampicillin, clindamycin, and tetracycline [15], cephalosporins [8], azithromycin, and erythromycin [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Enterococcus faecalis showed moderate sensitivity to Ampicillin with little sensitive to Rifampin but with subtile variations [26]. The E. faecalis showed sensitivity to Doxycycline and resistance to Erythromycin similar to those of Pinheiro and co-workers [42] while our Staphylococcus epidermides was sensitive to Gentamycin, Ciprofloxacin, Chloramphenicol, Rifampin, Amikacin and Tobramycin [43]; and the Staphylococcus xylosus showed resistance to Erythromycin; however, both bacteria resisted Erythromycine [44]. The variation in the resistance of bacteria to antibiotics depends upon species to another and strain to another due to different mechanism of action against antibiotics.…”
Section: Discussionsupporting
confidence: 48%
“…The main causes of treatment failure are the presence of persistent microorganisms and the recontamination of the canal due to inadequate sealing [4,5]. In the case of conventional endodontic treatment failure, retreatment, surgical endodontic treatment or extraction are carried out with the use of antibiotics and antiseptics as adjunctive therapies, but the long-term use of chemical antimicrobial agents, however, can be rendered ineffective by resistance developing in the target organisms [6][7][8].…”
Section: Introductionmentioning
confidence: 99%